2018
DOI: 10.1093/mmy/myx165
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology and management of candidemia in Northern Ireland during 2002−2011, including a 12-month enhanced case review

Abstract: In Northern Ireland there are concerns about candidaemia, with rates higher than those reported in England and Wales. Our aim was to explore the epidemiology of candidaemia during a 10 year period and the clinical management upon suspicion of cases during a one year enhanced investigation in Northern Ireland.Candidaemia reports to the Public Health Agency were validated during 2002-2011 and used to examine incidence and antifungal sensitivity trends (during 2007-2011). A clinical proforma was used to collate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
2
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 19 publications
2
13
2
1
Order By: Relevance
“…In contrast, the resistance rates in our study were lower than those in Nanjing [27]. Regarding other countries, the antifungal resistance rate in our study was higher than that reported in northern Ireland in 2007–2011 [36]. The resistance rate of azoles in C. albicans (< 5%) [40] worldwide was significantly lower than that in our study (> 20.0%).…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…In contrast, the resistance rates in our study were lower than those in Nanjing [27]. Regarding other countries, the antifungal resistance rate in our study was higher than that reported in northern Ireland in 2007–2011 [36]. The resistance rate of azoles in C. albicans (< 5%) [40] worldwide was significantly lower than that in our study (> 20.0%).…”
Section: Discussioncontrasting
confidence: 86%
“…Our studies showed that the ITR resistance rate was the highest, at 23.1% in all Candida species, followed by FCA (18.6%), VRC (18.5%) and 5-FC (4.1%). However, none of the isolates in this study were resistant to AMB, and the susceptibility results in our city were higher than those in northern Ireland (susceptibility, 99.1%) [36]. In China, the resistance rates vary significantly among different cities.…”
Section: Discussionmentioning
confidence: 69%
“…The incidence of 0.47 per 1,000 admissions (IQR 0.25–0.78) was similar to those reported in Australia [27], Belgium [28] and Spain [29] (0.21, 0.44 and 0.58 per 1,000 admissions, respectively) and lower than reported by Northern Ireland [30], Italy [31], Peru [18] and Brazil [19] (1.09, 1.73, 2.04, 2.49 per 1,000 admissions respectively). In a recent study that explored contributing factors for the Candida spp.…”
Section: Discussionsupporting
confidence: 85%
“…Despite the significant differences in the overall EQUAL scores, we were reassured that the 30‐day survival was similar across age groups in our setting. However, the overall 30‐day all‐cause mortality from candidaemia in our study was still high at 32% but lower compared to 41% in Scotland overall, 18 35.1% in Northern Ireland 19 and 38% in Europe 20 . The difference favouring survival of the younger patients in our study was significant at the 90‐day time point when compared to the very elderly patients.…”
Section: Discussioncontrasting
confidence: 65%